HUBUNGAN PEMBERIAN REWARD DENGAN MOTIVASI BELAJAR SISWA SD KELAS V GUGUS 1 KECAMATAN TAMPAN KOTA PEKANBARU - Siswati '; Mahmud Alpusari; Zufriady ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrak: The purpose of this study was to look at the relationship between reward the students' motivation class V Cluster 1 Kecamatan Tampan Kota Pekanbaru. This research is a quantitative research. The population in this study were students class V Cluster 1 Kecamatan Tampan Kota Pekanbaru numbering 395. The sampling technique used by the researchers is to use simple random sampling or simple random sampling. Researchers took a precision of 15% of the members of a population of 395 students using the formula of Taro Yamane so on can sample used was 102 students ClassV Cluster 1 Kecamatan Tampan Kota Pekanbaru. Techniques of collecting data in the form of questionnaires and interviews unstructured. Technical analysis of the data used is the product moment correlation technique. These results indicate that there is a positive and significant relationship between reward the students' motivation class V Cluster 1 Kecamatan Tampan Kota Pekanbaru. It is based on the analysis results obtained t hitung> t table or 9.925> 1.983. The relationship of reward to the students' motivation is at the level of the strong relationship because rxy of 0.7044 which entered the coefficient ranges from 0,60- 0,799. Large donations or contributions between reward the students' motivation Class V Cluster 1 Kecamatan Tampan Kota Pekanbaru is 49.7% This means that the reward system are some of the factors that can increase student motivation, and there are still other factors that 50.3% can affect students' motivation.Key Words: Reward, learning Motivation